Báo cáo tiếp thu, giải trình, chỉnh lý dự thảo Luật Đấu thầu (sửa đổi) (kèm theo báo cáo tóm tắt) - Quốc hội Khoá XV (2023)
Toàn văn Báo cáo tiếp thu, giải trình, chỉnh lý dự thảo Luật Đấu thầu (sửa đổi) (kèm theo báo cáo tóm tắt).